Herpes simplex virus type 1 DNA cleavage and encapsidation require the product of the UL28 gene: isolation and characterization of two UL28 deletion mutants. - Tengelsen, L A (1993)
The herpes simplex virus type 1 UL28 gene contains a 785-amino-acid open reading frame that codes for an essential protein. Studies with temperature-sensitive mutants which map to the UL28 gene indicate that the UL28 gene product (ICP18.5) is required for packaging of viral DNA and for expression of viral glycoproteins on the surface of infected cells (C. Addison, F. J. Rixon, and V. G. Preston, J. Gen. Virol. 71:2377-2384, 1990; B. A. Pancake, D. P. Aschman, and P. A. Schaffer, J. Virol. 47:568-585, 1983). In this study, we describe the isolation of two UL28 deletion mutants that were constructed and propagated in Vero cells transformed with the UL28 gene. The mutants, gCB and gC delta 7B, contained deletions of 1,881 and 537 bp, respectively, in the UL28 gene. Although the mutants synthesize viral DNA, they fail to form plaques or produce infectious virus in cells that do not express the UL28 gene. Transmission electron microscopy and Southern blot analysis demonstrated that both mutants are defective in cleavage and encapsidation of viral DNA. Analysis by cell surface immunofluorescence showed that the UL28 gene is not required for expression of viral glycoproteins on the surface of infected cells. A rabbit polyclonal antiserum was made against an Escherichia coli-expressed Cro-UL28 fusion protein. This antibody reacted with an infected-cell protein having an apparent molecular mass of 87 kDa. The 87-kDa protein was first detected at 6 h postinfection and was expressed as late as 24 h postinfection. No detectable UL28 protein was synthesized in gCB- or gC delta 7B-infected Vero cells.